Evaluation of mechanical properties of anatomically customized fiber posts using E-glass short fiber-reinforced composite to restore weakened endodontically treated premolars - Dawood Salman Dawood Alshetiwi; Nor Aidaniza Abdul Muttlib; Hatem M. El-Damanhoury; Rabihah Alawi; Normastura Abd Rahman; Nesrin Aly Elsahn; Mohmed Isaqali Karobari (BMC, 2024)
Abstract Objective This study was conducted to assess the influence of combining different forms of fiber-reinforced composites (FRC) on the mechanical behavior and bond strength of compromised endodontically treated teeth (ETT). Materials and methods Eighty extracted human premolar teeth were randomly divided into five experimental groups according to the type of intra-radicular restoration and the canal preparation design which was either non-flared (Group 1), flared (Groups 2-5), closed-apex (Groups 1,3,5) or open-apex (Groups 2,4). Standard prefabricated fiber posts were used as intra-radicular restoration for Groups 1-3 while Groups 4-5 were restored with anatomically customized relined fiber posts. After composite core fabrication, all samples were sent for an artificial aging process. Fracture resistance and push-out bond strength tests were then carried out through a universal testing machine followed by mode of failure analysis via a stereomicroscope and scanning electron microscope. Results Pairwise Log-Rank comparisons revealed that the survival rate of Group 2 and Group 3 was significantly lower than all other groups after artificial aging. The highest fracture resistance value (1796 N) was recorded in Group 5 and was significantly higher than that of the other groups (p < 0.05), while Group 2 exhibited the lowest fracture resistance (758 N), which was significantly lower compared to the other groups. Group 5 and Group 4 demonstrated a significantly higher push-out bond strength, at all root thirds, than Group 3, Group 2, and Group 1 (p < 0.05). The most frequently observed failure mode in the tested groups occurred between the resin cement and radicular dentin. Conclusion The use of short fiber-reinforced composite (SFRC) to reline the prefabricated FRC post has been proven to have superior fracture resistance with favorable failure patterns and increased push-out bond strength values compared to standard prefabricated FRC posts.